Hypoxia-elicited cardiac microvascular endothelial cell-derived exosomal miR-210–3p alleviate hypoxia/reoxygenation-induced myocardial cell injury through inhibiting transferrin receptor 1-mediated ferroptosis. (December 2022) - Lei, Dongyu; Li, Biao; Isa, Zuribia; Ma, Xiaoqiang; Zhang, Baojian
Abstract: Objective: Ferroptosis is a novel mode of non-apoptotic cell death induced by build-up of toxic lipid peroxides (lipid-ROS) in an iron dependent manner, which is a key event in ischemia/reperfusion (I/R)-induced cardiomyocytes damages. Studies indicated that ischemic preconditioning with cardiac microvascular endothelial cells (CMECs) protected against I/R-induced cardiomyocytes damages. However, the role of hypoxia-conditioned CMECs-derived Exo (H-exo) in I/R cardiomyocytes damages remains largely unclear. Therefore, the objective of this study was to explore the role and underlying mechanisms of H-exo in hypoxia/reoxygenation(H/R)-induced H9C2 cells damages. Methods: The rat CMECs were subjected to hypoxia or normoxia culture and Exo was subsequently collected and identified. H-exo or normoxia-conditioned CMECs-derived Exo (N-exo) were administered to H9C2 cells with H/R. To evaluate the therapeutic effect of H-exo and H-exo on H/R-induced H9C2 cells damages, cell proliferation was detected by CCK-8 assay and Edu staining, and ferroptosis process were evaluated by iron ion concentration, lipid reactive oxygen species (ROS) level, malondialdehyde (MDA) level, glutathione peroxidase (GSH-Px) level, and the protein expression of ferroptosis markers. Mechanically, we utilized the RT-qPCR to identify the expression of candidate miR-210–3p in N-exo and H-exo. Bioinformatics combined with dual luciferase reporter assay disclosed the downstream molecular mechanism of miR-210–3p. Results: The results indicated that both H-exo and N-exo significantly facilitated cell proliferation, increased GSH-Px levels and ferroptosis marker (GPX4) protein levels, and reduced iron ion concentration, lipid ROS level, MDA levels and ferroptosis markers (ACSL4 and PTGS2) protein levels in H/R-treated H9C2 cells. More importantly, the therapeutic effect of H-exo was significantly better than that of N-exo. Mechanistically, the results of RT-qPCR revealed significant enrichment of miR-210–3p in H-exo compared with N-exo. The miR-210–3p delivered by H-exo inhibited TFR expression by directly interacting with TFR mRNA, resulting in the promotion of cell proliferation and the attenuation of cell ferroptosis in H/R-treated H9C2 cells. Conclusion: All these data demonstrated that H-exo derived miR-210–3p facilitated the proliferation of myocardial cells in H/R-treated H9C2 cells by suppressing TFR-mediated ferroptosis, which provided new methods to treat H/R-induced myocardial injury. Graphical Abstract: ga1 Highlights: CMEC-derived exosomes especially H-exos can inhibit the H/R-induced ferroptosis to protect myocardial cells injury. The expression of miR-210–3p in H-exos was markedly higher than that in N-exos. H-exos derived miR-210–3p protects H/R-induced H9C2 cells damage by suppressing TFR-mediated ferroptosis.